Chloroplast genome variation and phylogeny of mutant Typhonium flagelliforme (Araceae) from Indonesia - NESTI FRONIKA SIANIPAR; ZIDNI MUFLIKHATI; ENDANG RAHMAT; REFLINUR REFLINUR; KHOIRUNNISA ASSIDQI; DWIYANTARI WIDYANINGRUM (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sianipar NF, Muflikhati Z, Rahmat E, Reflinur, Assidqi K, Widyaningrum D. 2025. Chloroplast genome variation and phylogeny of mutant Typhonium flagelliforme (Araceae) from Indonesia. Biodiversitas 26: 5703-5713. Typhonium flagelliforme (rodent tuber) is an indigenous Indonesian medicinal plant valued for its anticancer properties. Mutation induced by gamma irradiation have produced mutant accessions with enhanced bioactivity, yet the underlying genetic basis remains poorly understood. To address this gap, we conducted a comparative analysis of complete chloroplast genomes from wild-type and mutant T. flagelliforme. Both genomes displayed a typical quadripartite structure, with lengths of 167,195 bp (wild-type) and 167,204 bp (mutant). Gene annotation revealed 118 genes in the wild-type, but only 116 in the mutant, with the absence of psaL and petN, genes related to photosystem I and the cytochrome b6f complex. In addition to both accessions preferring A/U-ending codons, simple sequence repeat (SSR) profiling identified 131 motifs in the wild type and 132 in the mutant. Divergent hotspot analysis detected high nucleotide diversity in loci, such as ndhE and ccsA. Phylogenetic reconstruction confirmed that both accessions form a monophyletic clade closely related to T. blumei, reinforcing their genetic proximity within the genus. These findings demonstrate that induced mutation results in localized plastome alterations without disrupting overall structural stability, thereby providing valuable genomic resources for phylogenetic inference, biodiversity conservation, and marker-assisted breeding in Typhonium and related Araceae taxa.